Knowledge, Attitudes, and Practices of Healthcare Professionals Toward Internet-Based Hypertension Management: A Cross-Sectional Study - Zhang Y; Zhang Q; Ren Q; Wang Y; Wang J; Wu Y; Shang M; Zhou Y; Liu R; Li X; Wang Z; Wang F; et al. (Journal of Multidisciplinary Healthcare, 2025)
Yi Zhang,1 Qian Zhang,1 Qingsong Ren,2 Yongle Wang,3 Jihong Wang,1 Yuhong Wu,4 Moyu Shang,1 Yujing Zhou,1 Ran Liu,1 Xin Li,1 Zhanglin Wang,1 Fengxia Wang,1 Fengjuan Yuan1 1School of Nursing, Pingdingshan University, Pingdingshan, 467000, People’s Republic of China; 2Deputy chief physician of ICU of Pingdingshan First People’s Hospital, Pingdingshan, 467099, People’s Republic of China; 3Department of Cardiology, Pingdingshan First People’s Hospital, Pingdingshan, 467000, People’s Republic of China; 4Nursing Department of Pingdingshan First People’s Hospital, Pingdingshan, 467000, People’s Republic of ChinaCorrespondence: Jihong Wang, Email 13673759892@163.comObjective: Internet-based outpatient hypertension management offers a promising approach to improve treatment adherence and blood pressure control, yet its adoption remains suboptimal due to insufficient knowledge and inconsistent practices among healthcare professionals. This study aims to investigate the Knowledge, Attitude, and Practice (KAP) of healthcare professionals toward internet-based outpatient hypertension management.Methods: This cross-sectional study was conducted at 25 hospitals across China between 30 December 2023 and 12 January 2024. Healthcare professionals were recruited through the medical affairs and nursing departments. KAP scores was collected using a structured questionnaire. Data were analyzed using descriptive statistics, Pearson correlation, logistic regression, and structural equation modeling (SEM).Results: The study included 1, 199 valid questionnaire responses. Based on the 70% cutoff, 29.77% of the participants demonstrated adequate knowledge, 86.66% had positive attitudes, and 41.03% exhibited proactive practices. Significant positive correlations were observed between knowledge and attitude (r = 0.346, P < 0.001), knowledge and practice (r = 0.183, P < 0.001), and attitude and practice (r = 0.389, P < 0.001). Multivariate logistic regression revealed professional title and participation in hypertension management teams as key factors influencing knowledge and practice. Pearson correlation analysis revealed significant positive correlations between knowledge and attitude (r = 0.346, P < 0.001), knowledge and practice (r = 0.183, P < 0.001), and attitude and practice (r = 0.389, P < 0.001). Mediation analysis revealed that professional title directly affected knowledge (β = 0.248, P = 0.007) and indirectly influenced attitude (β = 0.247, P = 0.006) and practice (β = 0.073, P = 0.010). Additionally, participation in hypertension management teams directly affected practice (β = − 1.756, P = 0.020) while having indirect effects on attitude (β = − 0.355, P = 0.042) and practice (β = − 0.105, P = 0.025).Conclusion: Healthcare professionals demonstrated insufficient knowledge, positive attitudes, and suboptimal practices regarding internet-based outpatient hypertension management. These findings highlight the need for targeted training programs to enhance knowledge and practices and advocate for integrating digital strategies into routine clinical care. Strengthening healthcare professionals’ competencies in digital hypertension management is essential for improving patient outcomes and ensuring the sustainability of such interventions.Keywords: knowledge, attitude, practice, healthcare professional, hypertension, internet-based outpatient management, Cross-sectional study